Deciphering transcription factors and their corresponding regulatory elements during inhibitory interneuron differentiation using deep neural networks - Alatawneh, Rawan; Salomon, Yahel; Eshel, Reut; Orenstein, Yaron; Birnbaum, Ramon Y. (Frontiers in Cell and Developmental Biology, 2023)
During neurogenesis, the generation and differentiation of neuronal progenitors into inhibitory GABAergic interneurons is dependent on the combinatorial activity of transcription factors (TFs) and their corresponding regulatory elements (REs). However, the role of neuronal TFs and their target REs in inhibitory interneuron progenitors are not fully elucidated. Here, we developed a deep-learning-based framework to identify enriched TF motifs in gene REs (eMotif-RE), such as poised/repressed enhancers and putative silencers. Using epigenetic datasets (e.g., ATAC-seq and H3K27ac/me3 ChIP-seq) from cultured interneuron progenitors, we distinguished between active enhancer sequences (open chromatin with H3K27ac) and non-active enhancer sequences (open chromatin without H3K27ac). Using our eMotif-RE framework, we discovered enriched motifs of TFs such as ASCL1, SOX4, and SOX11 in the active enhancer set suggesting a cooperativity function for ASCL1 and SOX4/11 in active enhancers of neuronal progenitors. As opposed to the pro-neural ASCL1 activity toward differentiation of inhibitory GABAergic interneurons, we found an enriched motif of pro-neural NEUROG2 in the poise/repressed enhancer set, indicating its complementary function as repressor of REs in these progenitors. In addition, we also found enriched ZEB1 and CTCF motifs in the non-active set. Using in vivo enhancer assay, putative enhancers showed neuronal-specific enhancer activity while most of the tested putative REs from the non-active enhancer set showed no enhancer activity. Two of the eight REs (25%) showed function as poised enhancers in the neurons system. Moreover, mutated REs for ZEB1 and CTCF motifs increased their in vivo activity as enhancers indicating a repressive effect of ZEB1 and CTCF on these REs that likely function as repressed enhancers or silencers. Overall, our work integrates novel framework based on deep learning together with a functional assay that elucidated novel functions of TFs and their corresponding REs. Our approach can be applied to better understand gene regulation not only in inhibitory interneuron differentiation but in other tissue and cell types.